Diarylpropanes and lignans from Horsfieldia tetratepala. (March 2017) - Du, Shou-Zhen; Wang, Zhi-Chong; Liu, Ying; Zhan, Rui; Chen, Ye-Gao
Graphical abstract: Highlights: Horsfieldia, a Chinese traditional folk medicinal plant, was investigated for its chemical components. 7 compounds were isolated, including two new ones. Compounds 1 and 2 are new diarylpropanes. Abstract: Two new diarylpropanes (1 –2 ), four known compounds, and a new artifact, were isolated from 70% aqueous acetone extract of the twigs of Horsfieldia tetratepala . Their structures were elucidated by spectroscopic analysis. Cytotoxicity evaluation against five cancer cell lines showed that none of these compounds was cytotoxic.